- #1

- 40

- 0

solve for x,

a) (logx^3)^2 = logx^18

b) logx^3 + log(x^logx) = -2

so this is what i got so far:

a) (3logx)^2 = logx^18

9logx^2 = logx^18

18logx = logx^18

logx^18 = logx^18

... then i got stuck... i was clueless and did not know how to solve for x.

b) 3logx + (logx)(logx) = -2

logx^2 + 3logx +2 = 0

so let logx = s

s^2 +3s + 2 = 0

(s+1)(s+2)=0

s=-1 or s=-2

... then again i got stuck... I am not sure if what i did was right. our teacher gave us these questions that she has never taught us b4 and said this is ur assignment for the break... any help would be very much appreciated. thnx.

- Tu